2020
DOI: 10.1007/s10035-019-0989-0
|View full text |Cite
|
Sign up to set email alerts
|

Runout transition and clustering instability observed in binary-mixture avalanche deposits

Abstract: Binary mixtures of dry grains avalanching down a slope are experimentally studied in order to determine the interaction among coarse and fine grains and their effect on the deposit morphology. The distance travelled by the massive front of the avalanche over the horizontal plane of deposition area is measured as a function of mass content of fine particles in the mixture, grain-size ratio, and flume tilt. A sudden transition of the runout is detected at a critical content of fine particles, with a dependence o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 53 publications
0
2
0
Order By: Relevance
“…Model experiments were conducted with five different granular diameters and three different collapse masses [6] and obtained the similar results to Tochigi [5] in terms of mass centre. Furthermore, series of model tests was conducted that focused on the effect of the mixture of fine or coarse grains in rock debris on runout distance [7]. This study revealed that the observed runout distance reaches a maximal value when the volumetric ratio of coarse to fine grains exceeds 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Model experiments were conducted with five different granular diameters and three different collapse masses [6] and obtained the similar results to Tochigi [5] in terms of mass centre. Furthermore, series of model tests was conducted that focused on the effect of the mixture of fine or coarse grains in rock debris on runout distance [7]. This study revealed that the observed runout distance reaches a maximal value when the volumetric ratio of coarse to fine grains exceeds 50%.…”
Section: Introductionmentioning
confidence: 99%
“…Several factors affect rock avalanches' motion and sedimentary features and morphologies of the resulting deposit (Manzella and Labiouse, 2009;Phillips et al, 2006;Yang et al, 2011;Li et al, 2021; Landslide mobility and deposit morphology at various setting of source volume et al, 2019, 2022). However, the characteristics of structural geology in the source of a rock avalanche are significant controlling factors in modulating rock avalanches' propagation (Huang and Liu, 2009;Lucas and Mangeney, 2007;Bartali et al, 2020;Manzella and Labiouse, 2009;Phillips et al, 2006;Manzella and Labiouse, 2013b;Crosta et al, 2017;. It was stated that the existence of discontinuities could reduce the internal friction and further facilitate the long runout of the sliding mass (Lan et al, 2022;Corominas, 1996).…”
Section: Introductionmentioning
confidence: 99%